Visual failure without headache in idiopathic intracranial hypertension. Issue 2 (21st January 2005) - Lim, M; Kurian, M; Penn, A; Calver, D; Lin, J-P
Abstract : Aim: To determine the differences in outcome in a group of children with idiopathic intracranial hypertension (IIH) who do not present with headaches. Methods: Differences in epidemiological and aetiological factors, clinical presentation, and visual outcome were investigated in children with a diagnosis of IIH presenting with and without headaches to the Paediatric Neurology and Paediatric Ophthalmology Services at Guy's & St Thomas' Hospitals NHS Trust between 1997 and 2002. Results: Compared to the 29 children with headaches, the 12 children in the non-headache group were younger (7.3 v 9.5 years), presented with more neurological signs (33% v 10%), and were more likely to present with severe visual failure (33% v 4%), with a tenfold increased risk of an enlarged blind spot or field defects (50% v 5%). Permanent visual failure affected a third of all children in the non-headache group, but was rare in children presenting with headaches (33% v 3%), with one patient registered blind and two severely visually impaired. Conclusion: The management of IIH is difficult in the absence of headache. Visual surveillance is vital. These children were treated with an aggressive management programme to reduce cerebrospinal fluid pressure by repeated lumbar puncture, medication, and early surgical intervention if required. Non-invasive monitoring techniques might contribute to a better understanding of the natural history of IIH, improved management, and visual outcome.